(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
This article looks at the transition of a practical problem into one of knowledge, seeking to situate the first experiences of forerunners of psychiatry in the border area between Mexico and the United States, precisely at the time of an open struggle against drug dependence. Through career histories in hospitals, jails, and drug detoxification clinics, a context will be defined in which seven psychiatrists gained knowledge relative to the mentally ill in a region, which had psychiatric educational programs and institutions only by the end of the 20th century.